A bibliometric analysis of work engagement in the hospitality and tourism industry - Yao, Han; Ying, Yang; Mohamed, Rosmah (Emerald Publishing Limited, 2022)
Purpose: For the past two decades, researchers have been exploring knowledge of work engagement in the hospitality and tourism industry (HTI). This study aims to provide a comprehensive analysis of global research trends in the field through a bibliometric analysis. Design/methodology/approach: A total of 335 papers from 2005 to 2021 were searched using the Scopus database. The analysis focused on the temporal distribution, most productive journals, countries/territories, institutions, authors, international and authors' collaboration, the most cited publications and author keywords. The VOS viewer and R software were used to visualise the scientific landscapes. Findings: The results indicated a rapidly increasing trend of studies on work engagement in the HTI. The journal with the most published articles was the International Journal of Hospitality Management. The USA ranked first in production, and Karatepe, O.M., from Turkey was the leading author. The first and most cited article was from Salanova et al. (2005). Other themes were identified, mainly related to job resources and outcomes associated with work engagement. Practical implications: The study provides a more comprehensive understanding of the progress of work engagement in HTI studies and offers clues for further investigation in this field. Originality/value: This is the first paper to explore work engagement in the HTI using quantitative and visualised bibliometric analysis.